Energy efficiency : towards the end of demand growth - Sioshansi, Fereidoon P. (Elsevier Science/AP, 2013)
Energy efficiency is garnering re-focused public attention and re-invigorated funding. This volume addresses the full breadth of the field, from detailed guidance on implementation of new technologies to clear explanations of policy frameworks that can dictate which projects are profitable enough to deploy. The international expert contributions drawn together by F.P. Sioshansi feature the latest insights from recognized thought leaders, detailed examinations of evolving technologies, and practical case studies yielding best practices for project planners, implementers and financers.